Penerapan Metode Moora Pada Sistem Pemilihan Mutu Jenis Klon Atau Bibit Tanaman Karet (Studi Kasus: Balai Penelitian Sembawa, Palembang) - Dea Vitara; Widya Cholil (APTIKOM SUMSEL, 2021)
Rubber plants have a very important role for the Indonesian economy. Indonesia has a great opportunity to become a major rubber producer because it has very sufficient potential resources to increase production, both through expansion and replanting of plants with superior clones. South Sumatra Province is one of the largest rubber producers in Indonesia. Many farmers want to get the best rubber plants.The problem faced is how to choose the quality of the type of clone or the best rubber plant seeds. With a decision support system in analyzing the quality data of clone types or rubber plant seeds, one of them is by applying the MOORA (Multi-Objective Optimization by Ratio Analysis) method which is expected to produce the best prediction of the quality rank of clones. MOORA calculation method will be implemented in a web using MySQL.